1990
DOI: 10.1088/0022-3727/23/3/004
|View full text |Cite
|
Sign up to set email alerts
|

Development of electron swarms in SF6

Abstract: The electron swarm behaviour in SF6 is calculated and analysed for a wide range of E/N values from 71 to 5656 Td by both a Boltzmann equation method and a Monte Carlo simulation, using a set of electron collision cross sections determined by the authors. The Monte Carlo result shows clearly that the difficulty in deducing the electron energy distribution increases as the E/N values decrease due to a large electron attachment probability, while the result of the Boltzmann equation analysis shows that the set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
6
17
0
Order By: Relevance
“…A similar situation can be found in swarm analyses of electrons in SF 6 . Itoh et al 34 have found, using two-term and threeterm expansions of Boltzmann's equation, that the two-term approximation, as we have seen here, becomes increasingly inaccurate with E/N for values above about 1000 Td. Because of this we resort to Monte Carlo simulations in our C 2 F 4 swarm analyses.…”
Section: Discussion Of the Two-term Expansionsupporting
confidence: 53%
“…A similar situation can be found in swarm analyses of electrons in SF 6 . Itoh et al 34 have found, using two-term and threeterm expansions of Boltzmann's equation, that the two-term approximation, as we have seen here, becomes increasingly inaccurate with E/N for values above about 1000 Td. Because of this we resort to Monte Carlo simulations in our C 2 F 4 swarm analyses.…”
Section: Discussion Of the Two-term Expansionsupporting
confidence: 53%
“…In the present research, we were able to confirm that for CF 4 gas, an electron energy distribution with substantial changes in shape occurring very quickly in a nonequilibrium region or in equilibrium could be adequately represented. Thus, our method is likely to have broad applications.…”
Section: Results Of One-dimensional Samplingsupporting
confidence: 71%
“…The gas pressure was 1 torr, the gas temperature was 0 °C, and the set of Itoh and colleagues [4] was used for the electron collision cross-section. The gap length was 0.8 cm, the cathode was placed at x = 0 cm, and the electrode was assumed to be a wall completely absorbent to electrons.…”
Section: Computational Conditionsmentioning
confidence: 99%
“…One of the difficulties in using the Monte Carlo technique in a highly electron attaching gas such as SF6 is that the initial electrons released at the cathode get lost due to the high electron attachment cross section of SFe-as originally observed by Dincer and Govinda Raju [12]. The fate of the initial electrons in the simulation of Itoh et al [73] is shown in Figure 9. There are fluctuations in the parameters dependent on the distance from the cathode.…”
Section: The Boltzmann Equationmentioning
confidence: 93%